2015
DOI: 10.4103/1947-2714.163642
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of 10-year risk of coronary heart disease in nepalese patients with type 2 diabetes: Framingham versus United Kingdom prospective diabetes study

Abstract: Background:Predicting future coronary heart disease (CHD) risk with the help of a validated risk prediction function helps clinicians identify diabetic patients at high risk and provide them with appropriate preventive medicine.Aim:The aim of this study is to estimate and compare 10-year CHD risks of Nepalese diabetic patients using two most common risk prediction functions: The Framingham risk equation and United Kingdom Prospective Diabetes Study (UKPDS) risk engine that are yet to be validated for Nepalese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…As dyslipidemia is a well-established risk factor for cardiovascular diseases, presence of other co-variate risk factors results significantly higher risk of future CVD. This is in agreement with our earlier studies which have estimated higher risk of 10-year CHD among Nepalese type diabetic patients [43]. These findings warrant extensive preventive approaches, both clinical and non-clinical, to treat all types of dyslipidemia to minimize the future risk of CVD in our patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As dyslipidemia is a well-established risk factor for cardiovascular diseases, presence of other co-variate risk factors results significantly higher risk of future CVD. This is in agreement with our earlier studies which have estimated higher risk of 10-year CHD among Nepalese type diabetic patients [43]. These findings warrant extensive preventive approaches, both clinical and non-clinical, to treat all types of dyslipidemia to minimize the future risk of CVD in our patients.…”
Section: Discussionsupporting
confidence: 93%
“…The clustering of many of these risk factors often manifests as metabolic syndrome that precedes and then continues with the diabetes [42]. We have previously shown that Nepalese type 2 diabetic patients have high prevalence of metabolic syndrome and increased risk of CHD [43]. We also explored the covariate risk factors that were independently associated with dyslipidemia in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in our examination the UKPDS risk engine score classified 29.4% of individuals with DM2 at the high risk group. Higher risk in males was also found in other studies [5, 9]. Similarly, Kim et al [22] reported 24% of subjects at high CVD risk when using the UKPDS risk score algorithm in Korean adults with DM2.…”
Section: Discussionsupporting
confidence: 73%
“…In line with this, there are discrepant results obtained from many studies, showing that the different CVD risk algorithms have variable precision in different populations when distinguishing subjects who are at high-risk from the other ones [7, 8, 9, 10, 11, 12]. Moreover, a weak concordance between predicted and actual cardiovascular risk was also reported [13].…”
Section: Introductionmentioning
confidence: 99%
“…Determination of threshold, which was the percentage of the prediction of coronary heart disease refers to several considerations that were: a. the influence of a threshold value on the performance at level 1, level 2 and level 3, b. At the first stage is the screening stage, thus emphasizing the sensitivity performance parameter [8], c. refers to the percentage predicted incidence of coronary heart disease in the next 10 years, if values are <10% said to have low risk [18]. A number of these considerations used to analyze the results of testing at level 1.…”
Section: Resultsmentioning
confidence: 99%